Dra' Abu el-Naga, Ägypten. Untersuchungen zu Formation und Entwicklung einer oberägyptischen Residenznekropole. Die Arbeiten der Jahre 2017 und 2018 - Polz, Daniel; Böhme, Isa; Michels, Susanne; Ruppert, Christine (e-Forschungsberichte des DAI, 2018)
The institute’s archaeological work in the necropolis of Draʿ Abu el-Naga was temporarily concluded in 2017. The 2017–2018 seasons in the field primarily focused on the documentation of all accessible architectural and archaeological structures in Area H in Draʿ Abu el-Naga, the north-eastern part of the Theban Necropolis. Area H is located in the middle of the foothills of Draʿ Abu el-Naga and is the location of two widely visible landmarks: the remains of the mud-brick pyramid of king Nub-Kheper-Ra Intef (late 17th Dynasty, ca. 1580 BC), and the large twelve-pillared ‘Saff’ tomb no. 232 (TT 232, early 18th Dynasty, ca. 1550 BC). The surrounding area is characterized by an unusually large number of earlier, contemporary and later tombs and tomb shafts. For documentation purposes, both above and below ground, the structure from motion technique has been used.